Implementasi Multi Akad Dalam Transaksi Ekonomi Syariah - Setiadi, Setiadi; Hidayat, Asep Dadang; Ansori, Moh. Asep Zakariya; Athoillah, Mohamad Anton (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The renewal of muamalah contracts is very important for the development of more dynamic, progressive and innovative Islamic banking products, so that they can compete with existing conventional banking products. The purpose of this study was to examine the legal basis and design of these multiple contracts and their application in Islamic banking products. The method used in this research is library research. with research. The results of this study are that one of the constructive efforts that is very helpful in developing Islamic banking products is al-jam'u bainal uqud/multi contract, this is a new contract that has never been discussed in classical fiqh books. Scholars allow these multiple contracts as long as they do not violate Islamic principles and values ​​because the purpose of the contracts is to clarify rights and obligations and avoid tyranny that leads to the benefit of humans in this world and the hereafter. Multi contracts in musyarakah mutanaqishah products, namely, syirkah, ijarah, and buying and selling, these contracts form one product, in ijarah Muntiyah bit-tamlik, namely wa'd contracts (promises), ijarah and buying and selling also form one product. These contracts become integrated or there is ta'alluq or attachment and linkages between contracts. Keywords: Multi Contract, Musyarakah Mutanaqisah, Ijarah Muntakiya Bit-Tamlik